Impact of surface adhesion and sample heterogeneity on the multiscale mechanical characterisation of soft biomaterials - Megone, W. (Sci Rep, 2018)
The mechanical properties of soft materials used in the biomedical field play an important role on their performance. In the field of tissue engineering, it is known that cells sense the mechanical properties of their environment, however some materials, such as Sylard 184 PDMS (poly(dimethylsiloxane)), have failed to elicit such response. It was proposed that differences in the mechanical properties of such soft materials, at different scales, could account for these discrepancies. Indeed, the variation in the elastic moduli obtained for soft materials characterised at different scales can span several orders of magnitude. This called for a side-by-side comparison of the mechanical behaviour of soft materials at different scales. Here we use indentation, rheology and atomic force microscopy nanoidentation (using different tip geometries) to characterise the mechanical properties of PDMS, poly(acrylamide) (PAAm) and carboxymethyl cellulose (CMC) hydrogels at different length scales. Our results highlight the importance of surface adhesion and the resulting changes in contact area, and sample microstructural heterogeneity, in particular for the mechanical characterisation of ultra-soft substrates at the nano- to micro-scale.